Seamless integration of touch sensing smart textiles through computerized machine knitting - Md. Mohaddesh Hosen; Safi Ahmed (Journal of Engineered Fibers and Fabrics)
The recent advancements in smart textiles have led to a surge in the use of textile-based sensors to detect various signals, including touch, pressure, body temperature, humidity, and so on. Due to their flexibility, bendability, and lightweight design, all of which make them perfect for a variety of flexible sensing systems. Herein, a capacitive touch sensor consisting of all textile components has been architected through computerized machine knitting technology. The prototype has been realized with the double knit intarsia knitting technique, which enables seamless integration of touch sensing textiles onto non-conductive base fabric during single knitting operations. This simple and easily embedded touch interface enables users to experience soft and ultraflexible electronic textiles with high responsive (response time ~80 ms) sensing capabilities. High reproducibility and repeatability were observed with the manufactured capacitive touch sensor, with negligible change in capacitance within 500 touched-untouched cycles. The sensor also demonstrates outstanding flexibility against various mechanical deformations, that is, twisting, grasping, folding, and pinching. As a proof of concept, a machine knitted touch keyboard, numpad, wristband, and soft switch have been demonstrated as capacitive touch sensing user interfaces for human-machine interaction.